KOLABORASI PEMERINTAH DAERAH DAN UNIVERSITAS UNTUK OPTIMALISASI PENEMPATAN KERJA DI KABUPATEN KARAWANG - Yanuar, Muhammad Indra; Aditya, Indra; Priyanti, Evi (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The high number of educated unemployment in Karawang Regency, despite being the largest industrial area in Southeast Asia, is an irony that requires serious attention. This study aims to examine the collaboration between the Regional Government and Singaperbangsa University Karawang in optimizing job placement. The method used is qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study indicate that the synergy between the Manpower and Transmigration Office and the Special Job Exchange (BKK) of Singaperbangsa University Karawang has been quite effective through counseling programs, skills training, and the use of job search platforms. However, challenges still arise from the lack of readiness of individual job seekers, from administrative aspects to non-technical skills (soft skills). Strategic communication and ongoing coordination are key to creating adaptive and inclusive job placement policies. This study shows that optimal cross-sector collaboration can increase the absorption of local labor and strengthen the competitiveness of college graduates. These findings reinforce the importance of the Triple Helix approach in overcoming educated unemployment at the regional level.